An Engineered Cytochrome b(6)c(1) Complex with a Split Cytochrome b Is Able To Support Photosynthetic Growth of Rhodobacter capsulatus - Saribas, A. Sami (American Society for Microbiology, 1999)
The ubihydroquinone-cytochrome c oxidoreductase (or the cytochrome bc(1) complex) from Rhodobacter capsulatus is composed of the Fe-S protein, cytochrome b, and cytochrome c(1) subunits encoded by petA(fbcF), petB(fbcB), and petC(fbcC) genes organized as an operon. In the work reported here, petB(fbcB) was split genetically into two cistrons, petB6 and petBIV, which encoded two polypeptides corresponding to the four amino-terminal and four carboxyl-terminal transmembrane helices of cytochrome b, respectively. These polypeptides resembled the cytochrome b(6) and su IV subunits of chloroplast cytochrome b(6)f complexes, and together with the unmodified subunits of the cytochrome bc(1) complex, they formed a novel enzyme, named cytochrome b(6)c(1) complex. This membrane-bound multisubunit complex was functional, and despite its smaller amount, it was able to support the photosynthetic growth of R. capsulatus. Upon further mutagenesis, a mutant overproducing it, due to a C-to-T transition at the second base of the second codon of petBIV, was obtained. Biochemical analyses, including electron paramagnetic spectroscopy, with this mutant revealed that the properties of the cytochrome b(6)c(1) complex were similar to those of the cytochrome bc(1) complex. In particular, it was highly sensitive to inhibitors of the cytochrome bc(1) complex, including antimycin A, and the redox properties of its b- and c-type heme prosthetic groups were unchanged. However, the optical absorption spectrum of its cytochrome b(L) heme was modified in a way reminiscent of that of a cytochrome b(6)f complex. Based on the work described here and that with Rhodobacter sphaeroides (R. Kuras, M. Guergova-Kuras, and A. R. Crofts, Biochemistry 37:16280–16288, 1998), it appears that neither the inhibitor resistance nor the redox potential differences observed between the bacterial (or mitochondrial) cytochrome bc(1) complexes and the chloroplast cytochrome b(6)f complexes are direct consequences of splitting cytochrome b into two separate polypeptides. The overall findings also illustrate the possible evolutionary relationships among various cytochrome bc oxidoreductases.